Palladium‐Assisted Cleavage of Peptides and Proteins Containing a Backbone with Thiazolidine Linkage. Issue 42 (9th September 2016) - Jbara, Muhammad; Laps, Shay; Maity, Suman Kumar; Brik, Ashraf
Abstract: The design and synthesis of biomolecules that are responsive to external stimuli is of great interest in various research areas, such as in the preparation of smart biomaterial and chemical biology. Polypeptide backbone disassembly as a response to a particular stimulus is of interest, as it leads to a complete loss of the protein tertiary structure and, as a result, to a loss of function. In this study, a strategy based on palladium‐assisted efficient cleavage of backbone thiazolidine linkage in peptides and proteins was developed. Using a fluorescence‐based assay, encompassing ubiquitinated peptide with a quenching florescence pair, it was possible to optimize the cleavage step after rapid screening of various conditions, such as the type of metal complexes and reaction additives. The optimized conditions prompted fast cleavage of the thiazolidine linkage. The straightforward introduction of a backbone thiazolidine linkage in peptide and proteins coupled with the chemical methods used offers new opportunities in controlling macromolecule function and might, with the aid of cellular protein delivery methods, be applied in cellular settings. Abstract : Weak point to hit : Pd complexes enable rapid cleavage of thiazolidine linkages in peptide and protein sequences. The ability to control protein covalent structure may find useful applications in chemical biology and smart material.